Cathode material recovery method

The method of mixing sodium-ion-containing solutions with positive electrode material particles and subjecting them to heat treatment addresses the inefficiencies in lithium recovery from spent lithium secondary batteries, achieving efficient recovery with minimal lithium loss and reduced processing costs.

JP7670416B2Active Publication Date: 2025-04-30LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022577373
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-11
Filing Date
2021-09-09
Publication Date
2025-04-30
Estimated Expiration
2041-09-09

AI Technical Summary

Technical Problem

Current methods for recovering lithium from spent lithium secondary batteries are inefficient, as they require extensive processing to separate lithium from other components, leading to significant lithium loss and high costs.

Method used

A method involving the mixing of positive electrode material particles with a solution or powder containing sodium ions, followed by heat treatment, to remove fluorine components and minimize lithium loss, thereby recovering the positive electrode material in a form close to its original state.

Benefits of technology

This method effectively recovers positive electrode material with minimal lithium loss, reduces the amount of water required for washing, and maintains the durability of equipment, making the process more economical and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670416000006
    Figure 0007670416000006
  • Figure 0007670416000007
    Figure 0007670416000007
  • Figure 0007670416000008
    Figure 0007670416000008
Patent Text Reader

Abstract

The present invention relates to a method for recovering a cathode material from a cathode in a state close to its original shape, and when the present invention is used, it is possible to selectively remove only the fluorine component on the surface of the cathode material without losing the lithium component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0116722, filed on September 11, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a method for recovering a positive electrode material in a secondary battery, and more particularly, to a method for efficiently recovering a positive electrode material in a secondary battery in a state close to its original state by using a solution or powder containing sodium ions in a heat treatment step. [Background technology]

[0003] Lithium secondary batteries have the advantages of high energy density, large electromotive force, and the ability to store large amounts of energy, and are widely used in various industrial fields. For example, lithium secondary batteries are used in a variety of fields, from small portable devices such as smartphones and laptops to electric vehicles (EVs), which are expected to replace current fossil fuel vehicles in the future, and as a result, the amount of lithium secondary batteries that are disposed of due to their end of life is also on the rise.

[0004] Meanwhile, lithium, the most important component of lithium secondary batteries, is generally produced from ores containing lithium, and due to the cost of the manufacturing process and the price of the raw material itself, lithium metal is traded at a relatively high price. Therefore, there is a high demand not only for research on the performance of lithium secondary batteries themselves, but also for research on methods for efficiently recovering lithium from waste lithium secondary batteries, the amount of which is gradually increasing.

[0005] Currently, a well-known method for recovering lithium from a lithium secondary battery is to separate a positive electrode active material from the lithium secondary battery, dissolve the positive electrode active material powder in a sulfuric acid leaching process, and then separate various metals using a solvent extractant. However, in this case, a large amount of sodium compound is used in the extraction process, so it is difficult to finally separate sodium and lithium with high purity. In this case, since the lithium component is obtained in the form of a raw material, in order to use it again in a lithium secondary battery, a process of manufacturing the cathode material again from the beginning is required, which is disadvantageous in terms of economic efficiency. Therefore, recently, active research has been conducted on a direct recycling method in which the original form of the cathode material powder is removed and used again as a cathode material without performing the conventional recovery processes such as recovering the cathode material powder from a secondary battery or a cathode and leaching / extracting / purifying / crystallizing it. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] KR10-1682217 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention is intended to solve the problems of the conventional technology described above, and to provide a method for recovering a positive electrode material contained in a secondary battery in the form of the positive electrode material itself.

[0008] Specifically, the present invention provides a method for recovering a cathode material by mixing cathode material particles with a solution or powder containing sodium ions and then heat-treating the mixture, thereby minimizing the loss of lithium components in the cathode material while maximally removing fluorine components on the surface of the cathode material. [Means for solving the problem]

[0009] The present invention provides a method for recovering a positive electrode material, comprising: a step (S1) of obtaining positive electrode material particles from a positive electrode; a step (S2) of mixing the positive electrode material particles with a solution or powder containing sodium ions and then heat-treating the mixed positive electrode material particles; and a step (S3) of washing the heat-treated positive electrode material particles with water. Effect of the Invention

[0010] When the cathode material recovery method provided by the present invention is used, the cathode material particles are mixed with a solution or powder containing sodium ions, and then heat-treated, so that the fluorine component of the fluoropolymer binder remaining on the surface of the cathode material can be removed in the form of sodium fluoride, not lithium fluoride, and thus the cathode material can be recovered while minimizing the loss of lithium.

[0011] In addition, when the cathode material recovery method provided by the present invention is used, the generation of hydrogen fluoride, which can act as a strong acid during the heat treatment process, can be suppressed, and the cathode material can be recovered smoothly without adversely affecting the durability of the equipment. [Brief description of the drawings]

[0012] [Figure 1] 2 is a graph showing the results of XRD analysis of the powder obtained after the heat treatment in Example 1. [Diagram 2] 1 is a graph showing the results of an XRD analysis of the powder obtained after the heat treatment in Example 2. [Diagram 3] 1 is a graph showing the results of XRD analysis of the powder obtained after the heat treatment in Example 3. [Figure 4] 1 is a graph showing the results of an XRD analysis of the powder obtained after the heat treatment in Example 4. [Diagram 5] 1 is a graph showing XRD analysis of powder obtained after heat treatment in a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will now be described in further detail.

[0014] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0015] Cathode material recovery method The present invention provides a method for recovering a positive electrode material, comprising: a step (S1) of obtaining positive electrode material particles from a positive electrode; a step (S2) of mixing the positive electrode material particles with a solution or powder containing sodium ions and then heat-treating the mixed positive electrode material particles; and a step (S3) of washing the heat-treated positive electrode material particles with water.

[0016] The lithium recovery method of the present invention will be described step by step below.

[0017] Obtaining cathode particles (S1) The lithium recovery method of the present invention includes a step (S1) of obtaining positive electrode material particles from a positive electrode, for example, a positive electrode of a waste lithium secondary battery. In a lithium secondary battery, the positive electrode serves as a source of lithium ions, and a positive electrode active material, which is a lithium oxide-based compound, is bonded to a current collector as a binder to form the positive electrode. Since the object of the present invention is to recover the positive electrode material in its original form, in the present invention, after obtaining positive electrode material particles from the positive electrode, the particles are subjected to a positive electrode material recovery process.

[0018] On the other hand, the positive electrode active material of the positive electrode material is not particularly limited as long as it is an active material containing lithium element, and examples thereof include lithium nickel cobalt aluminum oxide (LiNiCoAlO2, NCA), lithium nickel cobalt manganese oxide (LiNiCoMnO2, NCM), lithium iron phosphate oxide (LiFePO4, LFP), lithium manganese iron phosphate oxide (LiMnFePO4, LMFP), lithium manganese oxide (LiMn2O4, LMO), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5Lithium oxide (LiCoO2, LCO), lithium cobalt oxide (LiCoO4, LNMO), lithium cobalt oxide (LiCoO2, LCO), etc. can be used as the positive electrode active material of the present invention. The positive electrode material particles in the present invention refer to particles containing a positive electrode active material, and specifically may be a powdered positive electrode material.

[0019] In this step, a specific method for obtaining the positive electrode material particles from the lithium secondary battery may include a step (S1-1) of crushing and pulverizing the positive electrode of the lithium secondary battery, and a step (S1-2) of classifying the crushed particles to separate the current collector particles and the positive electrode material particles. As described above, the positive electrode is present in a form in which the positive electrode material, i.e., the positive electrode active material, is mixed with a polymer binder and a carbon-based conductive material, etc. and coated on the current collector. Therefore, in the crushing and pulverizing step, the positive electrode active material coated on the current collector and some of the polymer binder and the carbon-based conductive material are detached, and in the subsequent classification step, the current collector particles pulverized together are separated from the positive electrode material particles. Body and The powdered positive electrode active material particles can be separated, and the separated positive electrode active material particles can be used as the positive electrode material particles of the present invention.

[0020] In the present invention, in order to recover and utilize the positive electrode material particles of the secondary battery in their original form to the greatest extent possible, it is necessary to separate the positive electrode material particles that are physically bound to the current collector, etc., through the crushing and classification steps described above. The positive electrode material particles obtained through the steps have a relatively uniform size of individual particles, and are therefore easily utilized even after final recovery.

[0021] The tap density of the positive electrode material particles obtained by this step may be 1.0 to 1.2 g / cc, and the average particle size may be 5 μm or more. Furthermore, based on the volume, the ratio of particles having a particle size of 5 to 10 μm in the particle size distribution of the obtained positive electrode material particles may be 2 to 10%, preferably 4 to 6%. The reason why the average particle size of the positive electrode material particles is in the above-mentioned range is that the positive electrode active material in the form of secondary particles is in a mixed form with a conductive material and a polymer binder. Furthermore, in the present invention, the current collecting ability of the positive electrode material particles that have been subjected to crushing and classification is body grainThe amount of contamination by particles can be 2000 ppm or less, preferably 1000 ppm or less, and impurities can be removed to the maximum extent possible during the crushing and classification steps.

[0022] Meanwhile, the specific method of crushing and classification is not particularly limited, and any means used for crushing and classification in the technical field can be applied to the present invention without any limitation. For example, the crushing can be performed by a general milling method such as a ball mill, a hammer mill, a jet mill, or a disk mill, and the classification can be performed using a device such as a cyclone classifier. In particular, the classification can be performed using a three-dimensional ultrasonic vibration classifier (twist screen) with different mesh sizes at the upper and lower ends. In this case, the current collector body grain Most of the particles are filtered through the sieve meshes at the upper and lower ends, while the positive electrode material particles pass through the sieve mesh at the lower end and can be collected and then used.

[0023] In addition, this step may be performed by a chemical solvent treatment method in addition to crushing and classification. Specifically, the polymer binder that bonds the cathode material and the current collector is easily dissolved in a solvent such as methylpyrrolidone (NMP) or dimethylacetamide (DMAC), so the cathode of the waste lithium secondary battery can be immersed in the above-mentioned solvent to separate the cathode material particles. However, since the cathode material particles are present in a form directly attached to the aluminum current collector, it may not be easy to stir using an impeller or the like in the chemical solvent treatment process, and the cathode material particles can be smoothly separated only if an additional process such as ultrasonic treatment is performed after immersion, but such an additional process may cause a problem of low process efficiency. Furthermore, after the chemical solvent treatment process, the polymer binder such as polyvinylidene fluoride (PVDF) is dissolved in the solvent, making it difficult to reuse the solvent, and even if it is reused, a purification process is required, which may be less economical, and a large cost may be incurred for disposing of the solvent.

[0024] This step may also be performed by a heat treatment method. Specifically, the heat treatment method may involve thermally removing the polymer binder that bonds the positive electrode material and the current collector, and then separating the positive electrode material particles from the current collector. When this step is performed by a heat treatment method, the temperature at which the heat treatment is performed varies depending on the type of polymer binder and the type of conductive material used in the manufacture of the positive electrode, and may be in the range of 450 to 500 ° C. based on PVDF, which is commonly used, and may be in the range of 500 to 550 ° C. when a carbon-based conductive material is used. There are no particular limitations on the equipment for performing the heat treatment method as long as it is equipped with a heating means, but it is particularly preferable to use a rotary heat treatment equipment such as a rotary kiln, since the exposed temperature gradient may become deeper due to stacking when a large number of secondary batteries are treated at once. However, when a heat treatment method is used, the mechanical properties of the current collector may deteriorate at high temperatures, and when rotation is involved in the heat treatment equipment, the physical impact may cause problems in that a large amount of fine current collector particles, for example, aluminum particles, may be mixed into the recovered positive electrode material.

[0025] Heat treatment step (S2) The cathode material particles physically separated from the cathode in the previous step are then heat-treated, specifically, in this step, the cathode material particles obtained in the previous step are mixed with a solution or powder containing sodium ions and then heat-treated.

[0026] In the case of the conventional technology, for example, the cathode material particles obtained by mechanical pretreatment or the like are dissolved in sulfuric acid, and then a solvent extractant is added to extract the metal components in the order of manganese, cobalt, and nickel, and the lithium component is recovered from the filtrate, thereby selectively recovering only the lithium component from among the components of the cathode material particles and reusing them. However, in this case, since each component used in the cathode material is separated and recovered, in order to manufacture the cathode material using the recovered components, the cathode material manufacturing process must be carried out from the beginning, and the process of separating each component from the cathode material also consumes a lot of cost and time, resulting in a problem of poor economic efficiency.

[0027] Therefore, in the present invention, an attempt is made to recover cathode material particles in a state close to their original state by selectively removing only the impurities while preventing the lithium component from leaching out of the recovered cathode material particles. The inventors of the present invention discovered that when the cathode material particles are mixed with a solution or powder containing sodium ions and then heat treated, the fluorine components on the surface of the cathode material, which make up a large proportion of the impurities, can be removed while minimizing the loss of the lithium component, making it possible to directly recover the cathode material particles, and thus completed the present invention.

[0028] Specifically, in the previous step of separating the cathode material particles from the cathode, some of the fluorine-based polymer binder remains on the surface of the cathode material. Unlike carbon, fluorine among the fluorine-based polymer binder components remaining on the surface of the cathode material is not easily combusted, so when the cathode material is treated at high temperatures, the fluorine component is not removed, but rather reacts with lithium in the cathode material components to form lithium fluoride. The lithium fluoride formed on the surface of the cathode material may act as an impurity in the recovered cathode material and should be removed by washing with water, etc., but since the solubility of lithium fluoride in water is low, a very large amount of water is required for washing with water, and additional lithium components are lost during the washing process. Therefore, when the cathode material is recovered by simply heat-treating the cathode material particles, the loss of lithium components is considerable and the cost of the recovery process is high, making it inefficient.

[0029] In contrast, when a solution or powder containing sodium ions is mixed with positive electrode material particles and heat-treated as in the present invention, the sodium ions react preferentially with the fluorine on the surface of the positive electrode material to form sodium fluoride, thereby reducing the amount of lithium component lost in the form of lithium fluoride. In addition, the solubility of sodium fluoride in water is 4.06% (based on 20°C), which is much higher than the solubility of lithium fluoride, 0.27%, so that the washing step can be performed with an even smaller amount of water. Furthermore, it is possible to prevent the fluorine on the surface of the positive electrode material from reacting with hydrogen to generate hydrogen fluoride, which is a strong acid, and the durability of the equipment can be maintained.

[0030] The solution or powder containing sodium ions used in this step is prepared using a sodium salt capable of generating sodium ions when dissolved, and the sodium salt may be alkaline, and may be one or more selected from the group consisting of NaOH, Na2CO3, and NaHCO3. When the solution or powder containing sodium ions is alkaline, it can neutralize hydrogen fluoride that may be generated during heat treatment to prevent corrosion of equipment, and when the above-mentioned sodium salt is used, the fluorine removal efficiency may be particularly high.

[0031] In this step, the positive electrode material particles are put into the solution or powder containing sodium ions, and then heat-treated. The amount of sodium in the solution or powder containing sodium ions is preferably equal to or greater than the number of moles of fluorine contained in the positive electrode material particles, based on the number of moles. The number of moles of sodium ions is preferably 150% to 200%, preferably 160% to 190%, and more preferably 170% to 180% of the number of moles of F. If the ratio of the number of moles of sodium to the number of moles of F is too low, the fluorine components on the surface cannot be sufficiently converted to sodium fluoride, and if the sodium concentration is too high, an excessive amount of sodium is used relative to the amount of sodium required, which is uneconomical.

[0032] In addition, when producing the solution containing sodium ions, it is preferable to produce it with a high-concentration sodium solution of 0.1 to 10M, preferably 5 to 10M. If the sodium concentration of the solution is too low, the solution may overflow when mixed with a solid-phase positive electrode material, resulting in a slurry. Conversely, if the sodium concentration of the solution is too high, sodium salts may precipitate in the solution. If the fluorine component on the surface of the positive electrode material cannot be sufficiently converted to sodium fluoride and the sodium concentration is too high, an excessive amount of sodium is used relative to the amount of sodium required, which is uneconomical.

[0033] In this step, the heat treatment may be performed in an oxygen-free atmosphere, and the oxygen-free atmosphere may have an oxygen concentration of 3% by volume or less, preferably 0 to 2% by volume, and more preferably 0 to 1% by volume. The oxygen-free atmosphere may be composed of one or more gases selected from nitrogen, carbon dioxide, and an inert gas. When the heat treatment is performed in an oxygen-free atmosphere, unnecessary reactions can be suppressed.

[0034] In this step, the heat treatment may be performed in an oxygen-excess atmosphere, and the oxygen-excess atmosphere may be an atmosphere having an oxygen concentration of 20% by volume or more, preferably 20 to 50% by volume, and more preferably 20 to 21% by volume. When the heat treatment is performed under conditions of an excess oxygen concentration, there is an effect that the carbon component of the positive electrode material is easily oxidized, and there is an advantage that the crystal structure of the positive electrode material is well maintained by preventing the consumption of lattice oxygen of the positive electrode material.

[0035] The temperature at which the heat treatment is performed in this step may be 250 to 800°C, preferably 300 to 650°C, and more preferably 300 to 500°C. When the heat treatment temperature is within the above range, components such as conductive material and binder remaining on the surface of the positive electrode material can be more efficiently removed. On the other hand, if the heat treatment temperature is higher than this range, local reduction may occur and the composition of the positive electrode material may crack, and if the heat treatment temperature is lower than this range, the carbon component of the positive electrode material may not be smoothly removed.

[0036] The heat treatment can be performed by increasing the temperature at a constant rate, holding the temperature for a certain period of time from the point where the temperature reaches a certain temperature, then increasing the temperature again at the same rate to a higher temperature and holding the temperature for a certain period of time again. For example, the heat treatment can be performed by increasing the temperature by 5°C per minute, holding the temperature for 0.5 hours from the point where the temperature reaches 350°C, then increasing the temperature again at the same rate to 450°C and holding the temperature for 0.5 hours. The temperature in the holding section is within the above-mentioned temperature range, and the heating rate may be 1 to 10°C per minute, preferably 3 to 7°C per minute. The holding time may be 0.3 to 1 hour, preferably 0.3 to 0.7 hours.

[0037] Water washing step (S3) The cathode material particles that have been heat-treated in the previous step can be washed with water and collected. Sodium fluoride is formed on the surface of the cathode material particles in the previous step, and the sodium fluoride on the surface has a certain degree of solubility in water, so it can be easily removed by washing with water.

[0038] The amount of water used for washing in this step can be significantly less than that in the case of heat treatment without using a solution or powder containing sodium ions, and as described above, in the present invention, the fluorine components on the surface of the cathode material are converted to sodium fluoride, which can be easily removed in the water washing step.

[0039] The cathode material particles recovered through this step can be used as a battery material without any additional treatment, and can be utilized while maintaining the composition ratio of the cathode active material when initially manufactured.

[0040] In the following, preferred examples are presented to aid in understanding the present invention, but the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0041] Example 1 After separating the positive electrode from the waste lithium secondary battery, it is crushed and classified to obtain powdered positive electrode particles (LiNi 0.6 Co0.2 Mn 0.2 O2) was obtained. 40 g of the obtained positive electrode material particles were mixed with 4 g of 50% NaOH aqueous solution and 14 g of distilled water, and then heat-treated. The heat treatment was performed by increasing the temperature by 5°C per minute, and from the point when the temperature reached 350°C, it was held for 0.5 hours, and then it was raised again to 450°C at the same rate and held for 0.5 hours. The heat treatment atmosphere was a nitrogen atmosphere, and nitrogen gas was injected at a rate of 200 cc per minute. The positive electrode material particles that had completed the heat treatment were naturally cooled, washed with water, and the recovered positive electrode material particles were obtained.

[0042] Example 2 The same procedure as in Example 1 was carried out except that 8 g of the NaOH aqueous solution was used, to obtain recovered positive electrode material particles.

[0043] Example 3 The same procedure was carried out as in Example 1, except that a solution containing sodium ions was used in which 2.65 g of Na2CO3 was mixed with 15.5 g of distilled water, and the positive electrode material particles were obtained.

[0044] Example 4 After separating the positive electrode from the waste lithium secondary battery, it is crushed and classified to obtain powdered positive electrode particles (LiNi 0.6 Co 0.2 Mn 0.2 O2) was obtained. 40 g of the obtained positive electrode material particles were mixed with 4 g of 50% NaOH aqueous solution and 14 g of distilled water, and then heat-treated. The heat treatment was performed by increasing the temperature by 5°C per minute, and from the point when the temperature reached 350°C, it was held for 0.5 hours, and then it was raised again to 450°C at the same rate and held for 0.5 hours. The heat treatment atmosphere was an oxygen-rich atmosphere, and oxygen gas was injected at a rate of 3 L / min per minute. The positive electrode material particles that had completed the heat treatment were naturally cooled, washed with water, and the recovered positive electrode material particles were obtained.

[0045] Comparative Example The same procedure was carried out as in Example 1, except that the positive electrode material particles were heat-treated without being mixed with a solution containing sodium ions, to obtain recovered positive electrode material particles.

[0046] Experimental Example 1. Confirmation of fluoride leaching rate and leached components in the examples and comparative examples The positive electrode material particles before the heat treatment in Example 1 were analyzed by ion chromatography (IC) to confirm the fluorine content in the positive electrode material particles before the heat treatment, and the fluorine content in the positive electrode material particles before the heat treatment was 1.51%, which was 604 mg based on 40 g of positive electrode material particles. Based on this value, the amount of fluorine leached from the positive electrode material particles after the heat treatment in the examples and comparative examples in the water washing process and the fluorine leaching rate were confirmed. Specifically, 150 g of distilled water was added to the total amount of positive electrode material particles obtained after the heat treatment, hand-shaken for 10 minutes, and filtered using a 0.2 μm syringe filter, and the fluorine content in the filtrate was confirmed by ion chromatography. The results are shown in Table 1 below, and in Table 1, the fluorine leaching rate is the amount of fluorine leached into 150 g of distilled water out of 604 mg of fluorine contained in 40 g of positive electrode material particles, expressed as a percentage.

[0047] [Table 1]

[0048] From the above results, it was confirmed that when the cathode material recovery method of the present invention is used, a large amount of fluorine components present on the surface of the cathode material is converted into sodium fluoride during the heat treatment process and can be easily leached into distilled water, thereby making it possible to save the amount of water used in the water washing process.

[0049] In particular, in the case of Comparative Example 1, the leaching rate was only 18.9%, and a large amount of fluorine remained on the surface of the positive electrode material particles, whereas in Examples 1 to 4 of the present invention, the leaching rates were all 30% or more, confirming that a large amount of fluorine was removed compared to the comparative examples. In particular, in the case of Example 2, in which sodium hydroxide was used as the sodium salt and the sodium concentration in the sodium salt was increased, the leaching rate was 80% or more, confirming that almost all of the fluorine could be easily leached and removed during the water washing process.

[0050] Furthermore, from a comparison of Examples 1 to 4, it was confirmed that when sodium hydroxide having a stronger alkalinity was used as the sodium salt, the fluorine leaching rate was high, and that a strongly alkaline sodium salt had a higher fluorine leaching efficiency than a weakly alkaline sodium salt. However, a strongly alkaline sodium salt compound has a higher reactivity than a weakly alkaline sodium salt compound, and requires special care in handling and storage, so it is self-evident that an appropriate type of sodium salt can be selected according to the required level of fluorine leaching rate.

[0051] Furthermore, the powders after the heat treatment in the above-mentioned Examples and Comparative Examples were subjected to XRD analysis to confirm the crystal phase of the fluorine compound in the powder. The XRD analysis graphs for Examples 1 to 4 are shown in Figures 1 to 4, and the XRD analysis graph for the Comparative Example is shown in Figure 5.

[0052] As can be seen from Figs. 1 to 4, in the examples, sodium fluoride (NaF) components were present, and thus the fluorine components of the positive electrode material particles were converted to the form of sodium fluoride and then removed during the water washing process. Meanwhile, in the case of Example 3, in which sodium carbonate was used as the sodium salt, as can be seen from Fig. 3, sodium carbonate was present in the leaching solution together with sodium fluoride, which indicates that some of the fluorine components could not react with sodium carbonate. This is linked to the results that the fluorine leaching rate in the previous Example 3 was lower than the fluorine leaching rates in Examples 1, 2, and 4, and indicates that when a sodium salt with relatively low alkalinity is used, the formation rate of fluorine compounds in the positive electrode material particles is lower than when a sodium salt with high alkalinity is used. Meanwhile, as can be seen from Fig. 5, in the comparative example, no sodium salt was used and sodium fluoride was not observed.

[0053] Experimental Example 2. Confirmation of the composition and characteristics of cathode material particles before and after heat treatment The compositions and characteristics of the cathode particles of Examples 1 to 4 and Comparative Example before and after a general heat treatment were confirmed. The heat treatment was carried out for 5 g of the cathode particles in an ambient atmosphere at 550° C. for 3 hours.

[0054] First, the lithium content in the positive electrode particles before and after heat treatment was analyzed by ICP-OES. The results are shown in Table 2. The reason why the lithium content increased during the heat treatment is believed to be because the fluoropolymer binder component present on the surface of the positive electrode particles and the carbon black used as a conductive material were burned and removed, resulting in an increase in the relative amount of lithium.

[0055] In addition, the amount of metal components leached when the positive electrode material particles were washed with water before and after the heat treatment was confirmed. Specifically, 5 g of the positive electrode material particles of Examples 1 to 4 and Comparative Example were taken, mixed and stirred with 100 g of distilled water, and the supernatant was taken and filtered using a syringe filter with a filter pore size of 0.45 μm. The filtrate was analyzed by ICP-OES to confirm the type and content of metal components leached into distilled water when the positive electrode material particles were washed with water before and after the heat treatment. The concentration of the metal components leached before the heat treatment or the result of converting this into a leaching rate is shown in Table 3 below, and the concentration of the metal components leached after the heat treatment or the result of converting this into a leaching rate is shown in Table 4 below.

[0056] Finally, the form of the lithium component leached as distilled water was confirmed. Specifically, the filtered leachate obtained from the heat-treated cathode material particles in the previous step was dried under reduced pressure at 68°C and 300 mbar, dried to 95% or more, and then collected in the form of powder. The crystal structure of the collected powder was analyzed by XRD. As a result of the analysis, Li2CO3 peaks and some LiF peaks were confirmed, and the results of analyzing the weight ratio by Rietveld refinement are shown in Table 5 below. This indicates that although some of the fluorine components can be removed by washing with water, the amount of lithium lost is considerable compared to the amount of fluorine removed. In particular, when the cathode material is collected without a process of mixing with a solution containing a sodium ion source and heat-treating it, the proportion of LiF, which has low solubility in the filtrate, is high, whereas in the cases of Examples 1 to 4, the proportion of LiF is relatively low. FIG. 1As can be seen from the results of Examples 1 to 4, in the cathode materials of Examples 1 to 4 after the heat treatment, a considerable portion of F exists as NaF. That is, since the proportion of LiF is low, the LiF fraction in the filtrate can be reduced, and NaF with high solubility is washed instead of LiF with low solubility, so that the amount of distilled water required for washing can be reduced. Side effects such as wastewater generation due to the use of an excessive amount of distilled water and secondary lithium leaching can be prevented. From the viewpoint of direct recycling, it can be confirmed that the target cathode active material can be produced only when lithium salt is added in the amount of leached lithium.

[0057] [Table 2]

[0058] [Table 3]

[0059] [Table 4]

[0060] [Table 5]

Claims

1. A step (S1) of obtaining positive electrode material particles from a positive electrode; A step (S2) of mixing the positive electrode material particles with a solution or powder containing sodium ions and then heat-treating the mixture; and (S3) washing the heat-treated cathode material particles with water, The method for recovering a positive electrode material, wherein the heat treatment is carried out in an oxygen-free atmosphere.

2. The step (S1) of obtaining the positive electrode material particles includes: A step (S1-1) of crushing and pulverizing a positive electrode of a lithium secondary battery; The positive electrode material recovery method according to claim 1, further comprising: a step (S1-2) of classifying the crushed particles to separate current collector particles and positive electrode material particles.

3. 3. The method for recovering a cathode material according to claim 1, wherein the step (S1) of obtaining the cathode material particles is carried out by a chemical solvent treatment method or a heat treatment method.

4. The method for recovering a positive electrode material according to claim 1 , wherein the solution or powder containing sodium ions has alkaline properties.

5. The sodium ion-containing solution or powder is NaOH, Na 2 CO 3 and NaHCO 3 The positive electrode material recovery method according to any one of claims 1 to 4, wherein the positive electrode material recovery method is produced using one or more selected from the group consisting of:

6. The method for recovering a positive electrode material according to any one of claims 1 to 5, wherein the amount of sodium in the solution or powder containing sodium ions is 150% to 200% relative to the number of moles of F.

7. The positive electrode material recovery method according to any one of claims 1 to 6, wherein the solution containing sodium ions has a sodium concentration of 0.1 to 10 M.

8. The positive electrode material recovery method according to claim 1 , wherein the oxygen-free atmosphere has an oxygen concentration of 3% by volume or less.

9. The method for recovering a positive electrode material according to claim 1 or 8, wherein the oxygen-free atmosphere is composed of one or more gases selected from the group consisting of nitrogen, carbon dioxide, and an inert gas.

10. The method for recovering a positive electrode material according to any one of claims 1 to 9, wherein the heat treatment carried out in the step (S2) is carried out at 250 to 800°C.

Citation Information

Patent Citations

  • Rotating thermal oxidation apparatus for recycling usage processing of battery

    JP2001250594A

  • Method for recovering active material from discarded battery material

    JP2012186150A

  • Method for separating and recovering positive electrode active material from lithium ion battery positive electrode material

    JP2013211234A

  • Method for processing fluorine-containing electrolyte

    JP2015092466A

  • Method of processing used lithium-ion battery

    JP2020129505A